2018
DOI: 10.1007/s11207-017-1232-y
|View full text |Cite
|
Sign up to set email alerts
|

On the Synchronizability of Tayler–Spruit and Babcock–Leighton Type Dynamos

Abstract: The solar cycle appears to be remarkably synchronized with the gravitational torques exerted by the tidally dominant planets Venus, Earth and Jupiter. Recently, a possible synchronization mechanism was proposed that relies on the intrinsic helicity oscillation of the current-driven Tayler instability which can be stoked by tidal-like perturbations with a period of 11.07 years. Inserted into a simple α − Ω dynamo model these resonantly excited helicity oscillations led to a 22.14 years dynamo cycle. Here, we as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 72 publications
2
31
0
Order By: Relevance
“…Moreover, analyzing Dicke's ratio iri2/i(riri1)2 (Dicke 1978) between the mean square of the residuals r i (defined as the distances between the actual minima and the hypothetical minima of a perfect 11.07‐year cycle) to the mean square of the differences r i − r i − 1 between two consecutive residuals, the solar cycle was shown to have much closer resemblance to a clocked process than to a random walk process (Stefani et al 2019). This gave further support for our conjecture (Stefani et al 2016, 2017, 2018, 2019) that the Schwabe cycle results from synchronizing a rather conventional α − Ω dynamo by means of an additional 11.07‐year oscillation of the α effect, which in turn is related to the helicity oscillation of either a kink‐type ( m = 1) Tayler instability in the tachocline region (Weber et al 2015) or a ( m = 1) magneto‐Rossby wave (Dikpati et al 2017; Zaqarashvili 2018). Building on and corroborating earlier ideas of Hung (2007), Scafetta (2012), Wilson (2013), and Okhlopkov (2014, 2016), the source of this synchronized helicity was hypothesized to be the 11.07‐year periodic tidal ( m = 2) forcing of Venus, Earth, and Jupiter, which are the tidally dominant planets in the solar system.…”
Section: Introductionsupporting
confidence: 87%
“…Moreover, analyzing Dicke's ratio iri2/i(riri1)2 (Dicke 1978) between the mean square of the residuals r i (defined as the distances between the actual minima and the hypothetical minima of a perfect 11.07‐year cycle) to the mean square of the differences r i − r i − 1 between two consecutive residuals, the solar cycle was shown to have much closer resemblance to a clocked process than to a random walk process (Stefani et al 2019). This gave further support for our conjecture (Stefani et al 2016, 2017, 2018, 2019) that the Schwabe cycle results from synchronizing a rather conventional α − Ω dynamo by means of an additional 11.07‐year oscillation of the α effect, which in turn is related to the helicity oscillation of either a kink‐type ( m = 1) Tayler instability in the tachocline region (Weber et al 2015) or a ( m = 1) magneto‐Rossby wave (Dikpati et al 2017; Zaqarashvili 2018). Building on and corroborating earlier ideas of Hung (2007), Scafetta (2012), Wilson (2013), and Okhlopkov (2014, 2016), the source of this synchronized helicity was hypothesized to be the 11.07‐year periodic tidal ( m = 2) forcing of Venus, Earth, and Jupiter, which are the tidally dominant planets in the solar system.…”
Section: Introductionsupporting
confidence: 87%
“…Yet another promising synchronization mechanism was first delineated by Weber et al (2015) and later corroborated in detail by Stefani et al (2016Stefani et al ( , 2018. It starts from the numerical observation that the current-driven, kink-type Tayler instability (TI) (Tayler, 1973;Pitts and Tayler, 1985;Gellert, Rüdiger, and Hollerbach, 2011;Seilmayer et al, 2012;Rüdiger, Kitchatinov, and Hollerbach, 2013;Stefani and Kirillov, 2015) has an intrinsic tendency for oscillations of the helicity and the α-effect related to it.…”
Section: Introductionmentioning
confidence: 92%
“…As a sequel to Stefani et al (2016Stefani et al ( , 2018, the present paper investigates this spatio-temporal behaviour of a tidally synchronized dynamo of the Tayler-Spruit type. For that purpose, we replace the ODE system by a partial differential equation (PDE) system with the co-latitude as the only spatial variable.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in Rüdiger et al (2011a, 2011b) it has been shown that for a constant current density in an infinitely long cylinder, the governing parameter is the Hartmann number, H a = B φ ( r out ) r out ( σ / ρ ν ) 1/2 , with σ , ρ , and ν being, respectively, the conductivity, density, and viscosity of the fluid, instead of Lundquist number S = H a P m 1/2 . Simulations at high Hartmann numbers (Stefani et al ; Weber et al ) have shown the production of helicity in Tayler instability that does not always decay to zero but may also saturate to a finite value, presenting in both cases new features like oscillations and limit cycles. While simulations are discovering an apparently broad family of saturation patterns, not much can be said from the analytical point of view.…”
Section: Basic Formalismmentioning
confidence: 99%
“…The effect of a finite Prandtl number has been investigated in cylindrical geometry (Rüdiger et al ), while the role played by a finite electrical resistivity in liquid conductor has been discussed in Weber et al (). A recent work in this direction (Weber et al ) discussed the numerical evidence that the saturation state of the Tayler instability at low magnetic Prantdl number and high Hartmann number is characterized by helicity oscillations: a result of important consequences if confirmed (Stefani et al ).…”
Section: Introductionmentioning
confidence: 99%